A Surge in Pediatric Coronavirus Disease 2019 Cases: The Experience of Texas Children's Hospital From March to June 2020. (10th December 2020) - Foster, Catherine E; Marquez, Lucila; Davis, Andrea L; Tocco, Elizabeth; Koy, Tjin H; Dunn, James; Revell, Paula A; Arrington, Amy S; Campbell, Judith R
Abstract: Background: An understanding of the clinical characteristics of children with coronavirus disease 2019 in diverse communities is needed to optimize the response of healthcare providers during this pandemic. Methods: We performed a retrospective review of all children presenting to the Texas Children's Hospital system with testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from March 10, 2020, through June 28, 2020. Demographics were recorded for all patients undergoing testing and clinical characteristics and outcomes were recorded for children with positive tests. Results: Of 16 554 unique patients ≤ 21 years of age who were tested for SARS-CoV-2, 1215 (7.3%) patients tested positive. Infants under 1 year of age and patients aged 18–21 years had the highest percent of positive tests at 9.9% (230/2329) and 10.7% (79/739), respectively. Hispanic children accounted for 66% (802/1215) of positive tests, though they only represented 42.1% (6972/16 554) of all children tested for SARS-CoV-2. Of the 1215 children with a positive test, 55.7% had fever, 40.9% had cough, 39.8% had congestion or rhinorrhea, 21.9% had gastrointestinal complaints, and 15.9% were asymptomatic. Only 97 (8%) patients were hospitalized (of which 68% were Hispanic). Most of the hospitalized patients had underlying medical conditions (62/97, 63.9%), including obesity. Thirty-one hospitalized patients (31/97, 32%) required respiratory support and 9 patients (9/97, 9.3%) received SARS-CoV-2 antiviral therapy. Two patients died. Conclusions: A relatively high percentage of Hispanic children tested positive for SARS-CoV-2 and were hospitalized. Most of the children with detection of SARS-CoV-2 had uncomplicated illness courses; some children were critically ill; and 2 patients died. Abstract : We describe the clinical characteristics and outcomes of children with SARS-CoV-2 infection in a health-care system in Texas. A high percentage of Hispanic children tested positive for SARS-CoV-2 and were hospitalized. Most of the children with SARS-CoV-2 infection had uncomplicated illness courses.